Thinking about ethnicity and gender diversity in children and young people. (April 2019) - de Graaf, Nastasja M; Manjra, Ilham I; Hames, Anna; Zitz, Claudia
Background: Little is known about how social and cultural variants interact with gender identity development. This article aims to identify the ethnicities of children and young people referred to the United Kingdom's national Gender Identity Development Service (GIDS), and compare the ethnicity data with the UK child population and referrals to Child and Adolescent Mental Health Services (CAMHS). Methods: GIDS referrals made between April 2012 and April 2015 for children and young people were retrieved. Ethnicity data were obtained by the '16 + 1' ethnicity list. Chi-square and t -tests were performed on the demographics. Results: Less than 10% of the 995 referrals at GIDS were from Black and minority ethnic (BME) groups – an underrepresentation as compared with both the national population and CAMHS figures. No significant differences in ethnic representation were found between the demographic birth-assigned sexes, across age groups, or year of referral. Conclusions: Hypotheses proposed for this underrepresentation take into account both the potential barriers to accessing services and the possibility of cross-cultural variations in the conceptualisations of gender, gender roles and gender diversity. Ethnicity, culture and religion, and their overlapping relationship with gender need further exploration.